Substantive Justice in Law Enforcement against Nominee Account Crimes from the Perspective of Aristotle and H.L.A. Hart's Philosophy: Keadilan Substantif dalam Penegakan Hukum terhadap Kejahatan Akun Nominee dalam Perspektif Filsafat Aristoteles dan H.L.A. Hart - Ginting, Beren Rukur; Wounde, Albert Huppy; Setyawan, Fendi; Amrullah, M. Arief (Rechtsidee, 2025)
General Background: The rapid development of financial systems and information technology has intensified complex economic crimes, including the misuse of nominee accounts to conceal beneficial ownership. Specific Background: In Indonesia, law enforcement often remains trapped in formalistic approaches that focus on nominal account holders, overlooking substantive perpetrators behind nominee structures. Knowledge Gap: This condition reveals a gap between formal legal responsibility and substantive justice, where moral culpability and true control over assets are insufficiently addressed in positive law enforcement practices. Aims: This study aims to analyze the application of substantive justice in handling crimes involving nominee accounts through the philosophical perspectives of Aristotle and H.L.A. Hart. Results: Using a normative-juridical and philosophical approach, the study finds that effective law enforcement should assess legal responsibility based on actual control, intent, and benefit, rather than mere formal ownership. Novelty: By integrating Aristotle’s concepts of distributive and corrective justice with Hart’s theory of legal rules and moral reasoning, this study offers a synthesized philosophical framework for penetrating legal formalism in nominee-related crimes. Implications: The findings imply the need for a paradigm shift in Indonesian law enforcement toward substantively just, morally grounded, and proportionate accountability to ensure that law functions as an instrument of genuine justice rather than procedural compliance alone. Highlights: Emphasizes the need to move beyond formal ownership toward identifying the true beneficial owner in nominee-based crimes. Integrates classical moral philosophy and modern legal theory to strengthen substantively just law enforcement. Highlights the urgency of reforming Indonesian legal practices to align legal certainty with moral accountability. Keywords: Substantive Justice, Nominee Accounts, Legal Formalism, Aristotle, H.L.A. Hart